Modules STEM-Based Science Learning Integrated with Education for Sustainable Development Materials on Environmental Pollution to Improve Science Literacy and Independent Learning - Novia Budiarti; Asri Widowati; Sabar Nurohman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to develop and evaluate a science learning module based on a STEM approach integrated with Education for Sustainable Development (ESD) on environmental pollution material for seventh-grade students. The research examined the module’s validity, practicality, and effectiveness in improving scientific literacy and learning independence. The development process employed the ADDIE model, while effectiveness testing used a quasi-experimental design with three groups: a STEM–ESD integrated module (experimental group), a STEM-only module, and an ESD-only module (comparison groups). The participants were seventh-grade students of SMPN 3 Sanggau Ledo. Data were collected using expert validation sheets, teacher and student response questionnaires, scientific literacy tests, and learning independence questionnaires. The results indicated that the module was categorized as very valid in terms of content, construction, and language, and very practical based on teacher and student responses. Effectiveness testing showed that the STEM–ESD integrated module resulted in higher improvements in scientific literacy compared to the STEM-only and ESD-only modules, with mean differences of 15.9 and 21.7, respectively. Statistical analysis using t-test and MANOVA revealed significant differences among the three groups (p < 0.05). In addition, students in the STEM–ESD group achieved the highest learning independence score (88.4%). In conclusion, the STEM–ESD integrated module is valid, practical, and statistically effective in enhancing scientific literacy and learning independence.